Copyright Protection for Digital Certificate using Blind Watermarking Technique - Hasan, Harith Raad (Kurdistan Journal of Applied Research, 2018)
This paper proposes a copyright protection system for digital certificate image using blind watermarking technique by applying discrete wavelet transform algorithm (DWT). The proposed technique utilizes three interrelated watermarks namely, Red watermark (RW), Green-watermark (GW) and Blue-watermark (BW). Firstly, RGB cover and RGB watermark image are divided for three color space R,G,B. Then the R component is chosen for embedding (RW), the B component is selected for embedding the (BW) and the G component is selected for embedding the (GW), R,G and B of the cover image are converted into the transform domain using DWT, and is subsequently decomposed into three levels viz. LH1, LL2 and LL3 sub-bands. RW, GW and BW are then embedded onto LL3. Experimental results show that the performance of the proposed technique is very encouraging with average PSNR of 44 db, and NCC value of more than 0.99 for extracted watermarks after performing several types of attacks.